Effect of Leptin on Marrow Adiposity in Ovariectomized Rabbits Assessed by Proton Magnetic Resonance Spectroscopy. Issue 4 (July 2018) - Li, Shaojun; Jiang, Hongning; Wang, Bo; Gu, Mingjun; Zhang, Ning; Liang, Wenwen; Wang, Yu
Abstract : Objective: Leptin acts to influence bone metabolism through indirect hypothalamic relay and direct peripheral pathways. Leptin enhances the differentiation of mesenchymal stem cells to the osteoblast rather than the adipocyte lineage, but the in vivo impacts of leptin on ovariectomy (OVX)-induced marrow adiposity are poorly understood. In this work, we aimed to address this question. Methods: Forty-five female New Zealand rabbits were divided into sham + vehicle, OVX + vehicle, and OVX + leptin for 5 months. Magnetic resonance spectroscopy and dual-energy x-ray absorptiometry were performed to longitudinally evaluate marrow fat fraction and bone density at 0, 2.5, and 5 months, respectively. At the end of experiment, quantitative parameters of marrow adipocytes were assessed by histopathology. Results: Estrogen-deficient rabbits markedly exhibited expansion of marrow fat in a time-dependent manner, with a variation of marrow fat fraction (+19.7%) at 2.5 months relative to baseline conditions, and it was maintained until 5 months (+49.2%; all P < 0.001), which was accompanied by diminished bone density. Adipocyte diameter, density, and adipocytes area percentage in the OVX controls was increased by 50.7%, 76.3%, and 135.5%, respectively, relative to the sham controls (all P < 0.001). These OVX-induced marrow adiposity and bone loss were partly restored by leptin treatment. Treatment with leptin prevented OVX-induced increases in bone turnover in rabbits. Conclusions: Early leptin administration inhibits the adipogenic effect of estrogen deficiency in terms of reverting marrow fat expansion seen in OVX rabbits. Magnetic resonance spectroscopy may be a useful tool for longitudinal and interventional assessments in osteoporosis.